EFEKTIFITAS PENAMBAHAN TEPUNG MAGGOT (HERMETIA ILLUCENS) SEBAGAI PENGGANTI TEPUNG IKAN DALAM RANSUM TERHADAP PERSENTASE DAGING NIRTULANG AYAM KAMPUNG UNGGUL BALITNAK (KUB): THE EFFECTIVENESS OF ADDING MAGGOT FLOUR (HERMETIA ILLUCENS) AS A SUBSTITUTE FOR FISH MEAL IN THE RATION ON THE PERCENTAGE OF BONELESS MEAT IN BALITNAK SUPERIOR VILLAGE CHICKEN (KUB) - Handarini, Ristika; Baharun, Abdullah; Rully Abdul Haq; Kardaya, Dede; Burhanudin Malik; Annisa Rahmi; Dewi Wahyuni (Jurnal Peternakan Nusantara, 2023)
Special local chicken feed is difficult to obtain in rural areas, so farmers use purebred chicken feed which is expensive and inefficient. This study aims to examine the effect of replacing fish meal with BSF (Hermetia ilucent) larvae on the growth of KUB chickens using local feed ingredients which can be seen from the boneless meat, bone, skin and the ratio of flesh to bone. This study used 100 KUB chickens. 20 units of litter cage. The materials used in this study were 100 KUB chicken DOC and the feed ingredients used corn, husk, BSF larvae flour, bread flour, CGF, soybean meal, fish meal, vegetable oil, premix, salt, and mineral mix. The rations were prepared using the Excel trial and error method based on nutrient requirements.This research was conducted for 75 days on April 1 – June 15, 2021 in Nambo village, Suka Jaya village, Tamansari sub-district, Bogor district, West Java. This study used a completely randomized design (RAL) with 5 treatments and 4 replications.Data analysis used one way ANOVA analysis and Duncan’s follow-up analysis. R0 = 0% BSF maggot flour in the ration, R1 = 25% BSF maggot flour replaces fish meal in the ration, R2 = 50% BSF maggot flour replaces fish meal in the ration, R3 = 75% BSF maggot meal replaces fish meal in the ration, R4 = 100% BSF maggot meal replaces fish meal in the ration. Based on the results of the analysis of variance, it had a significant effect (P<0.05) on the percentage of breastbone, the percentage of the thighbone, meat bone ratio of the chest and thigh but did not give a significant effect (P>0.05) on the percentage of the breast, the percentage of the thigh, the percentage of meat. without breastbone, percentage of meat without thighbone, percentage of breast skin and thigh skin. Replacing fish meal with BSF maggot flour in rations with the same nutritional balance was able to maintain the meat percentage and increase the percentage of KUB chicken bones.